2007
DOI: 10.1529/biophysj.107.111534
|View full text |Cite
|
Sign up to set email alerts
|

Domain Formation in Model Membranes Studied by Pulsed-Field Gradient-NMR: The Role of Lipid Polyunsaturation

Abstract: The effects of increased unsaturation in the sn-2 fatty acyl chain of phosphatidylcholines (PCs) on the lipid lateral diffusion have been investigated by pulsed-field gradient NMR. Macroscopically oriented bilayers containing a monosaturated PC, egg sphingomyelin, and cholesterol (CHOL) have been studied at temperatures between 0 degrees C and 60 degrees C, and the number of double bonds in the PC was one, two, four, or six. For PC bilayers, with and without the incorporation of egg sphingomyelin and CHOL, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
52
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(61 citation statements)
references
References 41 publications
9
52
0
Order By: Relevance
“…(5,15,21), which report factors of 2 to 10 depending on system details. In our simulations, the individual components can be easily traced.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…(5,15,21), which report factors of 2 to 10 depending on system details. In our simulations, the individual components can be easily traced.…”
Section: Resultsmentioning
confidence: 99%
“…Linoleic acid is a representative of the important class of 6 fatty acids. Experimentally, it has been shown that the presence of polyunsaturated tails increases the tendency to form domains (15,16).…”
mentioning
confidence: 99%
“…Fast exchange between domains has similarly been inferred from 2 H NMR spectra for deuterium labeled phospholipid in 18:0-22:6PC/18:0-22:6PE/18:0-22:6PS/cholesterol (4:4:1:1 mol), on the basis of which a radius of <250Å was assigned to 18:0-22:6PC/cholesterol clusters (Huster et al, 1998), and for deuterium labeled cholesterol in 16:0-18:1PC/brain SM/cholesterol (1:1:1 mol) (Aussenac et al, 2003). Intriguingly, recent pulsed field gradient (pfg) NMR measurements on PC/egg SM/cholesterol (3:3:2 mol) membranes aligned between glass plates suggest that the presence of PUFA can trigger the formation of large (>m) from small domains (Filippov et al, 2007). These experiments using PC with a 18:0 acid sn-1 chain revealed two lipid lateral diffusion coefficients, assigned to l o and l d phases, when 20:4 or 22:6, but not 18:1 and 18:2, acid was at the sn-2 position.…”
Section: Dha Domainsmentioning
confidence: 99%
“…[22,27,39] According to this idea, less free volume of bilayers (tighter packing of lipids) must lead to less translational mobility of lipid molecules and to higher activation energy of the diffusion process. Free volumes of DPPC and PSM have been determined previously by computer simulation [16] and by bilayer compressibility.…”
Section: Discussionmentioning
confidence: 99%
“…The PFG NMR method has proven to be very efficient in detecting structural and dynamic heterogeneities in lipid bilayers. [23,25,27,31] …”
Section: Introductionmentioning
confidence: 99%